Comparing costs and cost‐efficiency of platforms for micronutrient powder (MNP) delivery to children in rural Uganda. Issue 1 (24th June 2021) - Schott, Whitney; Richardson, Belinda; Baker, Emily; D'Agostino, Alexis; Namaste, Sorrel; Vosti, Stephen A.
Abstract: Micronutrient powder (MNP) can reduce iron deficiency in young children, which has been well established in efficacy trials. However, the cost of different delivery platforms has not been determined. We calculated the cost and cost‐efficiency of distributed MNP through community‐based mechanisms and in health facilities in a primarily rural district in Uganda. An endline survey ( n = 1072) identified reach and adherence. During the 9‐month pilot, 37, 458 (community platform) and 12, 390 (facility platform) packets of MNP were distributed. Each packet consisted of 30 MNP sachets. In 2016, total costs were 277, 082 (community platform, 0.24/sachet) and 221, 568 (facility platform, 0.59/sachet). The cost per child reached was lower in the community platform (53.24) than the facility platform (65.97). The cost per child adhering to a protocol was 58.08 (community platform) and 72.69 (facility platform). The estimated cost of scaling up the community platform pilot to the district level over 3 years to cover approximately 17, 890 children was 1.23 million (scale‐up integrated into a partner agency program) to 1.62 million (government scale‐up scenario). Unlike previous estimates, these included opportunity costs. Community‐based MNP delivery costs were greater, yet more cost‐efficient per child reached and adhering to protocol than facility‐based delivery. However, total costs for untargeted MNP delivery under program settings are potentially prohibitive. Abstract : This study estimates costs based on programmatic elements using two delivery platforms in a single rural site in Uganda: (1) delivery by community health workers (community‐based platform) and (2) delivery using facility‐based health providers (facility‐based platform). We calculated the cost of micronutrient powders (MNP) provision from start‐up to the "last mile"— the final leg in product and service delivery when MNP reaches beneficiaries. We compared costs and cost‐efficiency across delivery platforms using several indicators of outcomes and estimated the costs of scaling up, extending the pilot program, and integrating MNP delivery activities into existing infant and young child feeding programs.